Tetrapropylammonium-manganese oxide/polypyrrole hybrid nanocomposite thin films as novel electrode materials for supercapacitors - Chin, Suk Fun; Pang, Suh Cem (Elsevier, 2010)
Tetrapropylammonium-manganese oxide/polypyrrole (TPA-MO/Ppy) hybrid nanocomposite with molar ratios of TPA-MO/Ppy 4:1, 2:1 and 1:1 were successfully prepared by a combination of in situ polymerization and the sol–gel process. The microstructure of hybrid nanocomposite thin film samples was observed to be significantly affected by synthesis parameters, most notably the molar ratio of reactants and post-synthesis calcination temperature. Samples with higher pyrrole contents appeared to possess higher specific surface areas, which ranged from 132 to 281m2 g−1. SEM micrographs indicated that all nanocomposite thin films were highly fibrous and porous in nature. Optimum doping of manganese oxide with conducting polypyrrole had led to the formation of novel nanocomposite with nanofibrillar structures which consisted of interconnected manganese oxide and polypyrrole nanoclusters. Optimized nanocomposite films showed higher charge capacities which could be attributed to enhanced material utilization as a result of optimized microstuctural parameters in particular, specific surface areas